Online journalism : - Foust, James C. (Holcomb Hathaway, 2009)
The second edition of Online Journalism helps you apply your developing journalistic skills to the Internet. It reviews the basic principles (such as objectivity, fairness and accuracy) while showing you how to put these principles into practice online. Key features of the book include practical activities at the end of each chapter, screenshots illustrating key concepts, a Glossary and a companion Web site. The book's major themes and topics include: actual practices of online journalism, such as designing Web pages, writing and editing stories online and using links; hands-on guidance in text formatting with CSS; coverage of user-generated content, including citizen or participatory journalism and expanded information on blogging; discussion of the role of podcasts, syndication and RSS feeds, and social networking sites in journalism; a chapter on gathering and editing images, audio and video for use online; exploration of opportunities and challenges, including legal and ethical issues. The book's accompanying Web site is designed to enhance your learning experience. It provides useful links to additional original content and reference sources, examples, online tutorials and much more. The site will allow you to explore topics in greater detail, using links that are interesting and, in many cases, fun. The book's marginal QuickLinks identify linked resources. Online Journalism and its companion Web site will introduce you to the Internet's capability to take journalism in new, exciting directions directions that are more inclusive and more participatory. The book's combination of basic technological information, practical application and examples make it a perfect reference guide as you help this medium reach its full potential.